2001
DOI: 10.1021/jp0110152
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength Dependence of Photooxidation vs Photofragmentation of Chromocene

Abstract: Photooxidation and metal-ligand photolysis reactions of bis(cyclopentadienyl)chromium, chromocene, in the range 24 390-15 630 cm -1 are studied in the gas phase by using time-of-flight mass spectroscopic detection. Photooxidation of the intact chromocene molecule unexpectedly dominates in the range 23 530-24 000 cm -1 . The relative importance of photooxidation compared to photofragmentation is strongly wavelength dependent. A prominent species at all wavelengths is the chromium ion, but in a wavelength region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 52 publications
3
26
0
Order By: Relevance
“…Only for chromocene has a low-resolution molecular REMPI spectrum containing one broad structureless band been obtained. 24 On the other hand, recently we have demonstrated that ferrocene, 25,26 nickelocene, 27 and 1 28 can be efficiently ionized with nanosecond laser pulses when the transition from the metallocalized 3d z 2 orbital to the lowest Rydberg p x,y level is used as the first step of the multiphoton excitation. The REMPI spectrum of 1 28 revealed a structured Rydberg transition with wellresolved vibronic components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only for chromocene has a low-resolution molecular REMPI spectrum containing one broad structureless band been obtained. 24 On the other hand, recently we have demonstrated that ferrocene, 25,26 nickelocene, 27 and 1 28 can be efficiently ionized with nanosecond laser pulses when the transition from the metallocalized 3d z 2 orbital to the lowest Rydberg p x,y level is used as the first step of the multiphoton excitation. The REMPI spectrum of 1 28 revealed a structured Rydberg transition with wellresolved vibronic components.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of MPD, the REMPI spectra of sandwich compounds revealed peaks corresponding to the electronic transitions in the metal atoms. Only for chromocene has a low-resolution molecular REMPI spectrum containing one broad structureless band been obtained …”
Section: Introductionmentioning
confidence: 99%
“…For example, Cr(Cp)(C 3 H 3 ) and Cr(C 3 H 3 ) have been reported as stable fragments in the gas-phase laser photochemistry of chromocene. 27 Also, a stable YC 3 H 3 product has been observed by Davis et al 28 in the reaction of yttrium with 2-butyne. The formation and stability of small lanthanide carbides or metallocarbon clusters (LnC n ) have also been reported.…”
Section: Resultsmentioning
confidence: 83%
“…Structures similar to Ln­(Cp)­(C 3 H 3 ) and Ln­(C 3 H 3 ) have been identified in other work. For example, Cr­(Cp)­(C 3 H 3 ) and Cr­(C 3 H 3 ) have been reported as stable fragments in the gas-phase laser photochemistry of chromocene . Also, a stable YC 3 H 3 product has been observed by Davis et al in the reaction of yttrium with 2-butyne.…”
Section: Resultsmentioning
confidence: 95%
“…Only the lowest frequency component (21,000 cm −1 ) has been definitely assigned in literature in terms of a d -d transition ( 3 E 2g → 3 E 1g , 3 E 2g , 3 A 1g , 3 A 2g ). Based on this, band I is due to an electronic transition from the HOMO to the LUMO [87][88][89]. The d -d character of transition I is easily explained by considering that both the HOMO and the LUMO are primarily metal in character (d xy,x 2 −y 2 for the HOMO and dxz,yz for the LUMO) [90].…”
Section: Determination Of the Electronic Structure Of Cp 2 Cr By Combmentioning
confidence: 99%